Tinjauan Pemanfaatan Data Sensus Harian Rawat Inap - Febrina Sirait; Iman Anugrah Selamat Hura (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
A hospital is a health service institution that provides plenary individual health services that provide inpatient, outpatient, and emergency services. (Dzulhidayat, 2022). Minister of Health of the Republic of Indonesia number 24 of 2022 Medical Record is a document that contains patient identity data, examinations, treatment, actions, and other services that have been provided to patients.The daily inpatient census is a routine activity carried out in hospitals that counts the number of patients served in the inpatient unit. The daily inpatient census is conducted from 00:00 to 24:00 by officers in the care ward. The ward officer counts the number of incoming patients, outgoing patients, transferred or transferred patients, deceased patients and days of patient care. . The data will be recapitulated every month and used as statistics on hospital services that will be reported to the authorities. (Garmelia et al., 2018). The method in this research is a literature study, where this research is carried out with a data set technique to study books A literature search of records and reports related to research with the results obtained still found the implementation of the daily census of hospitalizations that are still delayed due to inadequate human resources In the absence of socialization to fellow officers, SOPs governing the daily census have not been implemented properly. This is why most of the daily census process of hospitalizations has not been well implemented